Evaluating the Tahfidzul Qur’an Program Based on the Context, Input, Process, and Product Model - Reni Marlena; Sumaryati; Nurus Amzana; Jang Bermano Putra; Nasution; Mohd Iqbal Haqim Mohd Nor (GHAITSA : Islamic Education Journal, 2026)
This study aims to evaluate the implementation of the Tahfidzul Qur'an Program at the Qur'an House in Lubuklinggau City by using the CIPP (Context, Input, Process, Product) evaluation model. This model was chosen to obtain a comprehensive picture of the functioning of the program in the context of community-based non-formal education. The research approach used is qualitative descriptive, employing data collection techniques such as interviews, observations, and documentation of program implementers, ustadz/ustadzah, students, and student guardians. The results of the study show that this program exists in response to the community's need for an accessible and flexible Qur'an education, especially in urban areas. In terms of context, the program is aligned with the religious mission of the community and local needs. The input components include the readiness of teaching staff dominated by the younger generation, a flexible curriculum, and adequate but straightforward infrastructure. The learning process is carried out by the muroja'ah, talaqqi method, and a memorization recording system that involves the active role of parents. The product evaluation revealed consistent student memorization, albeit with varying levels, and the formation of religious character in students. This study concludes that community-based tahfidz programs like this can be a strategic alternative in strengthening children's non-formal Islamic education and Qur'an literacy.